A Treatise on Testing General Linear Hypothesis in Stochastic Linear Regression Model - Narayana, C.; Mahaboob, B.; Venkateswarlu, B.; Ravi sankar, J.; Balasiddamuni, P. (International Journal of Engineering and Technology, 2018)
The main objective of this research article is to propose test statistics for testing general linear hypothesis about parameters in stochastics linear regression model using studentized residuals, RLS estimates and unrestricted internally studentized residuals. In 1998, M. Celia Rodriguez -Campos et.al [1] introduced a new test statistics to test the hypothesis of a generalized linear model in a regression context with random design. Li Cai et.al [2] provide a new test statistic for testing linear hypothesis in an OLS regression model that not assume homoscedasticity. P. Balasiddamuni et.al [3] proposed some advanced tools for mathematical and stochastical modelling.Â Â